Physician Experience in Technical Success of Achieving NPVR ≥ 80% of High-Intensity Focused Ultrasound Ablation for Uterine Fibroids: A Multicenter Study - Gong, Xue; Zhang, Xinyue; Liu, Dang; Yang, Chao; Zhang, Rong; Xiao, Zhibo; Chen, Wenzhi; Chen, Jinyun (Frontiers in Medical Technology, 2022)
Objective To evaluate the influence of physician experience on the technical success in high-intensity focused ultrasound (HIFU) ablation of uterine fibroids. Methods Patients from a 20-centre prospective study. Among the 20 clinical centers, 5 centers had physician with more than 3-years of HIFU experience, and the other 15 centers initiated HIFU therapy less than 3-years, were defined as the experienced group and the inexperienced group respectively. Technical success was compared in two groups, and that defined as achieving non-perfused volume ratio (NPVR) ≥ 80% of uterine fibroids with no major complications. Results A total of 1352 patients were included, at the age of (41.32 ± 5.08). The mean NPVR of (87.48 ± 14.9) % was obtained, (86.50 ± 15.76) % in the inexperienced group and (89.21 ± 13.12) % in the experienced group, respectively. In the experienced group, 82.20% of uterine fibroids obtained NPVR ≥ 80%, compared with 75.32% in the inexperienced group, the difference was significant (P = 0.003). The technical success rate of 82.00% in the experienced group, higher than that of the inexperienced group 75.20% (P = 0.004). Conclusions Inexperienced physicians and experienced physicians all can reach NPVR ≥ 80% and technical success rate ≥ 75%. The NPVR and technical success rate of experienced physicians was superior to that of inexperienced physicians.